Effectiveness of Acupuncture Point ANMIAN in the Treatment of Insomnia: A Case Series - Ferdin, Paul; Sekar, Beula; Venkatachalam, Kavitha; C P, Syam Kumar (Indian Journal of Integrative Medicine, 2024)
Insomnia is a prevalent sleep disorder that affects energy, mood, health, and overall quality of life. The intricate relationship between sleep and metabolism can lead to significant health issues when disrupted. Chronic insomnia and short sleep duration are linked to increased risks of various chronic conditions and higher mortality rates. This study reports on five patients presenting with insomnia at the Outpatient department, of the International Institute of Yoga and Naturopathy Medical Sciences, Chengalpattu. Each patient received acupuncture targeting the anmian points, with each 30-minute session administered five days a week for two weeks. Patients included are a 26-year-old male, a 68-year-old female, an 18-year-old female, a 47-year-old male, and a 65-year-old male, all experiencing severe insomnia with varying comorbidities. Results: Post-treatment, all patients reported significant improvements in sleep duration and quality, extending to nearly seven hours per night and reducing nighttime awakenings. Pittsburgh Sleep Quality Index (PSQI) scores showed substantial reductions, indicating mild insomnia. Improvements in daytime functioning were also noted. We meticulously monitor the patient for one month to ensure sustained effects. Acupuncture targeting the anmian points effectively improved sleep duration and quality in patients with severe insomnia, demonstrating its potential as a viable treatment for enhancing sleep and overall well-being.